Band gap tailoring of hydrothermally synthesized WS2 nanoparticles by the sulfurization time duration. Issue 18 (15th September 2021) - Ali, Hafiz T.; Jacob, Jolly; Ikram, Salma; Sikandar, Tariq; Mahmood, K.; Yusuf, Mohammad; Ali, A.; Amin, N.; Javaid, K.; Abolaban, Fouad A.
Abstract: In current study, WS2 nanoparticles were systematically synthesized by hydrothermal method. After successful growth, the effect of sulfurization time duration on various optical parameters such as band gap, absorbance, admittance and refractive index was investigated by sulfurization the grown samples for different time durations (0–1 h). XRD patterns have confirmed the pure phase formation of WS2 nanoparticles having crystallite size in the range of 24.4–29.26 nm. SEM images showed the flakes like structures which becomes more visible in combination with rectangular shapes when sulfurization time duration was increased. Synthesized WS2 nanoparticles have been further studied to see their optical properties as a function of sulfurization time duration. All the synthesized samples showed high absorption and low transmission in UV/near visible region at wavelength of 550 nm. By increasing the sulfurization time duration, crystallinity of sulfurized nanoparticles increased which resulted in the decreases of transmission. Optical parameters such as refractive index and the extinction coefficient were also found to be greatly affected by sulfurization. Optical band gap of synthesized nanomaterials have been found to decreases from 2.98 to 2.19eV with increasing sulfurization time duration.